EFFECTIVE IMPLEMENTATION OF PERSONAL CARD FOR FORMING POSITIVE STUDENT BEHAVIOR IN SMA STATE 6 PADANGSIDIMPUAN - Nor Mita Ika Saputri (Universitas Muhammadiyah Tapanuli Selatan, 2016)
This thesis entitled